Ethanolamines as Corrosion Inhibitors for Zinc in (HNO3+H2SO4) Binary Acid Mixture - R. T. Vashi; H. M. Bhajiwala; S. A. Desai (E-Journal of Chemistry)
This work deals with the study of corrosion behaviour for zinc in (HNO3+ H2SO4) binary acid mixture containing ethanolamines. Corrosion rate increases with concentration of acid and temperature. At constant acid concentration, the inhibition efficiency of ethanolamines increases with the inhibitor concentration. Value of ΔGa increases and inhibition decreases with temperature. The mode of inhibition action appears to be chemisorption.